One-Step Hydrothermal Synthesis of TiO2 Nanotubes and Photodegradation Activity towards Diazinon - Haryati, Tanti; Diana, Alvina Nur; Sofiyah, Ovy; Nelumbium, Tusiana Putri; Andarini, Novita; Sulistiyo, Yudi Aris; Suwardiyanto, Suwardiyanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
The study aimed to analyze how variations in TiO2/NaOH mole ratio, stirring time, and washing pH affect the formation process of TiO2 nanotubes (TNT) through one-stage hydrothermal. TiO2 micro powder was mixed with 10M NaOH with the variation of TiO2/NaOH mole ratio (0.005:1, 0.015:1, and 0.025:1). The hydrothermal process was then conducted at 130 ℃ in an autoclave for 24 h with stirring time intervals of 10, 15, and 20 minutes/h. The samples underwent 1 M HCl washing to produce diverse pH variations (pH = 2, pH = 3, and pH = 4). Characterization of the synthesized TNT was conducted using SEM, TEM, XRD, SAA, and UV-Vis DRS. After analysis of the micrographs revealed the fiber shape of the particles, it was noted that TNT particle size increased due to smaller mole ratio variation, longer stirring, and lower pH. The synthesized TNT featured a tubular morphology with an inner diameter of 3.30 nm, an outer diameter of 6.15 nm, and a wall thickness of 1.64 nm. The increase in sodium titanate content of the sample results in an increase in surface area. Additionally, small pore size contributes towards an increase in both surface area and total pore size. The best result of the TNT photocatalytic test against diazinon can be observed in the fifth sample with a mole ratio of 0.025:1, stirring time of 20 minutes/h, and washing pH of 3. With an irradiation time of 210 min, diazinon degradation reached 90%. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).